Method for removing impurities in tantalum powder by using mixed acid

Through the three-stage pickling treatment method of mixed acid and ultrasonic wave, the problem of difficult removal of metal impurities in tantalum powder is solved, and Cr and Fe impurities are efficiently removed, and the quality and production efficiency of capacitor-grade tantalum powder are improved.

CN119237729APending Publication Date: 2025-01-03CHINA ZHENHUA GRP XINYUN ELECTRONICS COMP ANDDEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411343092.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing pickling method is difficult to effectively remove metal impurities in tantalum powder, resulting in low capacitor performance, and increasing the acid concentration will damage the tantalum powder and reduce the yield.

Method used

Three-stage pickling treatment method using mixed acid and ultrasonic waves, including the first stage of ultrasonic removal, the second stage of high-temperature ultrasonic removal and the third stage of normal temperature ultrasonic removal, combined with rinsing, suction filtration and drying steps, acetic acid and The ratio of acids such as sulfuric acid and ultrasonic vibrations deeply remove Cr and Fe impurities in tantalum powder.

Benefits of technology

It significantly improves the removal rate and yield of tantalum powder, reduces production costs, and improves the quality and production efficiency of capacitor-grade tantalum powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005060257000000081
    Figure BDA0005060257000000081
Patent Text Reader

Abstract

The invention discloses a method for removing impurities in tantalum powder by using mixed acid. The method comprises the following steps: performing first-stage ultrasonic impurity removal treatment on the tantalum powder in a solution A; s2, performing second-stage high-temperature ultrasonic impurity removal treatment on the tantalum powder treated in the step S1 in a mixed acid solution; thirdly, the tantalum powder treated in the second step is subjected to third-stage normal-temperature ultrasonic impurity removal treatment in mixed acid liquor; finally, the tantalum powder is rinsed, subjected to suction filtration and dried. According to the method, a mixed acid and ultrasonic pickling mode is adopted, due to the particularity of ultrasonic, acid liquor can enter the tantalum powder more easily, metal in the tantalum powder can fully react with the acid liquor, the yield of tantalum powder products is guaranteed while a large amount of metal such as Cr and Fe is removed, and the method is suitable for industrial production. Therefore, the quality of the capacitor-grade tantalum powder is effectively improved, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tantalum powder processing, and in particular relates to a method for removing impurities in tantalum powder by using mixed acid. Background Art

[0002] A large amount of Cr and Fe metal impurities will be introduced in the production process of capacitor-grade tantalum powder by mechanical production. Some of these metal impurities are attached to the surface of tantalum powder, and some are embedded in the interior of tantalum powder or alloyed with tantalum. High metal impurities will affect the performance of tantalum powder and tantalum capacitors. In tantalum powder, the main body leakage current K value is large and the breakdown voltage is low. In tantalum capacitors, it is reflected in large leakage current, low pass rate and short service life. Basically, all manufacturers of capacitor-grade tantalum powder will use acid pickling to remove metal impurities. Ordinary acid pickling methods cannot effectively remove metal impurities. Simply increasing the concentration of acid will cause too much tantalum powder to be corroded, resulting in a low yield of the product. How to better remove metal impurities and ensure the yield has become the focus of research.

[0003] The patent document with the announcement number CN114472883A discloses a manufacturing process of tantalum particles. The process mainly includes the following steps: the first step is to select raw materials for graded crushing to obtain skeleton tantalum powder and ultrafine tantalum powder, the second step is to wash and remove impurities from the crushed tantalum powder, the third step is to dry the ultrafine tantalum powder and freeze-dry the skeleton tantalum powder, the fourth step is to granulate by spraying, the fifth step is to sinter, crush and granulate, and the sixth step is to reduce oxygen. The technical content of this patent is to remove magnesium oxide and excess magnesium, and to use the corresponding acidic solution for impurity removal.

[0004] The patent document with the announcement number CN118460860A discloses a leaching method of nickel-based high-temperature alloy, including: ultrasonic activation: ultrasonic activation of nickel-based high-temperature alloy with hydrofluoric acid; acid leaching: leaching the nickel-based high-temperature alloy after ultrasonic activation with hydrofluoric acid with acid, liquid-solid separation, and obtaining a leachate; the acid is selected from hydrochloric acid with a concentration of 1-8 mol / L, sulfuric acid with a concentration of 1-4 mol / L, or aqua regia. The patent adopts the method of ultrasonic activation with hydrofluoric acid and acid leaching to allow the valuable elements in the nickel-based high-temperature alloy to enter the solution and improve the leaching rate; but the relevant content of removing impurities from tantalum powder is not disclosed. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for removing impurities in tantalum powder by using mixed acid.

[0006] The present invention is achieved through the following technical solutions.

[0007] The present invention provides a method for removing impurities from tantalum powder by using mixed acid, comprising the following steps:

[0008] S1: subjecting tantalum powder to the first stage of ultrasonic impurity removal treatment in solution A;

[0009] S2: subjecting the tantalum powder treated in step S1 to a second high-temperature ultrasonic impurity removal treatment in a mixed acid solution;

[0010] S3: The tantalum powder treated in step S2 is then subjected to a third stage of ultrasonic impurity removal treatment at room temperature in a mixed acid solution; finally, the tantalum powder is rinsed, filtered, and dried.

[0011] Preferably, the solution A in step S1 is an acetic acid solution with a concentration of 2% to 10%, which is stirred for 10 min to 15 min at 100 r / min to 180 r / min and 50° C. to 80° C., and ultrasonic high-frequency vibration of 20 KHz to 35 KHz is added during the treatment process.

[0012] Preferably, the mixed acid solution in step S2 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 7% to 13%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 20 to 40:1.

[0013] Preferably, in step S2, pickling is carried out under stirring at 100 r / min to 180 r / min and 50° C. to 80° C. for 2 h to 4 h, and ultrasonic high-frequency vibration of 20 KHz to 35 KHz is added during the treatment process.

[0014] Preferably, the mixed acid solution in step S3 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 3% to 9%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 20-40:1.

[0015] Preferably, in step S3, pickling is carried out under stirring at 100 r / min to 180 r / min and 50° C. to 80° C. for 2 h to 4 h, and ultrasonic high-frequency vibration of 20 KHz to 35 KHz is added during the treatment process.

[0016] Preferably, the rinsing in step S3 is performed after the acid solution is poured out, deionized water is added to the tantalum powder and stirred evenly before pouring out the liquid.

[0017] Preferably, the filtration in step S3 includes the following steps: using a filter membrane to be laid in a filtration device, pouring the powder after rinsing onto the filter membrane, and vacuuming the solution to pass through the polypropylene filter membrane, and the powder remains on the filter membrane to achieve solid-liquid separation; by continuously adding deionized water to the filtration device to dilute the acid content in the powder until the conductivity of the filtered liquid is ≤50μs / cm, stopping the addition of deionized water, and draining the liquid in the powder.

[0018] Preferably, the filter membrane is a polypropylene filter membrane with a pore size of 2 μm to 10 μm, and the conductivity of the added deionized water is ≤0.5 μs / cm.

[0019] Preferably, the drying in step S3 comprises the following steps: placing the filtered powder into a vacuum oven at 120-180° C. for 3-9 hours.

[0020] The beneficial effects of the present invention are:

[0021] Due to the surface tension of the liquid, the acid cannot enter the interior of the tantalum powder very well, and some metal impurities in the tantalum powder cannot be removed in conventional pickling. If the concentration of the mixed acid is simply increased, the concentration of the acid entering the tantalum powder becomes higher, which can achieve the effect of removing impurities, but the high-concentration acid also corrodes the tantalum powder seriously during the pickling process, resulting in large losses, and the yield of the tantalum powder product is low, which greatly increases the production cost. The method of the present invention adopts a mixed acid plus ultrasonic pickling method. Due to the particularity of the ultrasound, the acid is easier to enter the interior of the tantalum powder, so that the metal inside the tantalum powder can fully react with the acid, and while a large amount of metals such as Cr and Fe are removed, the yield of the tantalum powder product is also guaranteed, thereby effectively improving the quality of capacitor-grade tantalum powder and improving production efficiency. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below, but the scope of protection claimed is not limited to the description.

[0023] Embodiment 1:

[0024] A method for removing impurities from tantalum powder using mixed acid comprises the following steps:

[0025] S1: The capacitor-grade tantalum powder is subjected to the first stage of ultrasonic impurity removal treatment in solution A, and acetic acid is first used to remove the organic matter wrapped around the tantalum powder, so that the surface of the tantalum powder is more exposed to the acid solution;

[0026] S2: subjecting the tantalum powder treated in step S1 to a second high-temperature ultrasonic impurity removal treatment in a mixed acid solution to achieve an impurity removal effect;

[0027] S3: The tantalum powder treated in step S2 is then subjected to a third stage of ultrasonic impurity removal treatment at room temperature in a mixed acid solution to achieve a further impurity removal effect; finally, the tantalum powder is rinsed, filtered, and dried.

[0028] In the two mixed acid treatments, hydrofluoric acid first destroys the oxide layer on the tantalum surface, and non-oxidizing acid sulfuric acid can better remove Cr metal. Adding ultrasonic vibration can better open the pores of tantalum powder, allowing the acid to enter the interior of tantalum powder, allowing the metal impurities inside the tantalum powder to fully react with the mixed acid, achieving the effect of significantly reducing metal impurities such as Cr and Fe.

[0029] In step S1, solution A is a 2% acetic acid solution, which is stirred at 100 r / min and 50° C. for 10 min, and 20 KHz ultrasonic high-frequency vibration is added during the treatment process.

[0030] The mixed acid solution in step S2 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 7%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 20:1.

[0031] In step S2, pickling is performed with stirring at 100 r / min and 50° C. for 2 h, and ultrasonic high-frequency vibration of 20 KHz is added during the treatment.

[0032] The mixed acid solution in step S3 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 3%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 20:1.

[0033] In step S3, pickling is carried out under stirring at 100 r / min and 50° C. for 2 h, and 20 KHz ultrasonic high-frequency vibration is added during the treatment process.

[0034] The rinsing in step S3 is after the acid liquid is poured out. Since the acid liquid cannot be poured out completely, 10L of deionized water needs to be added to the tantalum powder and stirred evenly before pouring out the liquid to reduce the concentration of the remaining acid liquid.

[0035] The filtration in step S3 includes the following steps: using a filter membrane to be laid in a filtration device with a diameter of 350 mm, pouring the powder after rinsing onto the filter membrane, vacuuming the solution to pass through the polypropylene filter membrane, and leaving the powder on the filter membrane to achieve solid-liquid separation; by continuously adding deionized water to the filtration device to dilute the acid content in the powder until the conductivity of the filtered liquid is ≤50μs / cm, stopping adding deionized water and draining the liquid in the powder.

[0036] The filter membrane is a polypropylene filter membrane with a pore size of 2 μm and a diameter of 350 mm, and the conductivity of the added deionized water is ≤0.5 μs / cm.

[0037] The drying in step S3 comprises the following steps: pouring the filtered powder into a 304 stainless steel disc with a diameter of 300 mm, and placing it in a vacuum oven at 120° C. for 3 hours.

[0038] Embodiment 2:

[0039] A method for removing impurities from tantalum powder using mixed acid comprises the following steps:

[0040] S1: The capacitor-grade tantalum powder is subjected to the first stage of ultrasonic impurity removal treatment in solution A, and acetic acid is first used to remove the organic matter wrapped around the tantalum powder, so that the surface of the tantalum powder is more exposed to the acid solution;

[0041] S2: subjecting the tantalum powder treated in step S1 to a second high-temperature ultrasonic impurity removal treatment in a mixed acid solution to achieve an impurity removal effect;

[0042] S3: The tantalum powder treated in step S2 is then subjected to a third stage of ultrasonic impurity removal treatment at room temperature in a mixed acid solution to achieve a further impurity removal effect; finally, the tantalum powder is rinsed, filtered, and dried.

[0043] In the two mixed acid treatments, hydrofluoric acid first destroys the oxide layer on the tantalum surface, and non-oxidizing acid sulfuric acid can better remove Cr metal. Adding ultrasonic vibration can better open the pores of tantalum powder, allowing the acid to enter the interior of tantalum powder, allowing the metal impurities inside the tantalum powder to fully react with the mixed acid, achieving the effect of significantly reducing metal impurities such as Cr and Fe.

[0044] In step S1, solution A is a 10% acetic acid solution, which is stirred at 180 r / min and 80° C. for 15 min, and 35 KHz ultrasonic high-frequency vibration is added during the treatment process.

[0045] The mixed acid solution in step S2 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 13%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 40:1.

[0046] In the step S2, the pickling is carried out by stirring at 180 r / min and 80° C. for 4 hours, and 35 KHz ultrasonic high-frequency vibration is added during the treatment process.

[0047] The mixed acid solution in step S3 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 9%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 40:1.

[0048] In step S3, the pickling is carried out under stirring at 180 r / min and 80° C. for 4 hours, and 35 KHz ultrasonic high-frequency vibration is added during the treatment process.

[0049] The rinsing in step S3 is after the acid liquid is poured out. Since the acid liquid cannot be poured out completely, 15L of deionized water needs to be added to the tantalum powder and stirred evenly before pouring out the liquid to reduce the concentration of the remaining acid liquid.

[0050] The rinsing in step S3 is after the acid liquid is poured out. Since the acid liquid cannot be poured out completely, 10L of deionized water needs to be added to the tantalum powder and stirred evenly before pouring out the liquid to reduce the concentration of the remaining acid liquid.

[0051] The filtration in step S3 includes the following steps: using a filter membrane to be laid in a filtration device with a diameter of 350 mm, pouring the powder after rinsing onto the filter membrane, vacuuming the solution to pass through the polypropylene filter membrane, and leaving the powder on the filter membrane to achieve solid-liquid separation; by continuously adding deionized water to the filtration device to dilute the acid content in the powder until the conductivity of the filtered liquid is ≤50μs / cm, stopping adding deionized water and draining the liquid in the powder.

[0052] The filter membrane is a polypropylene filter membrane with a pore size of 10 μm and a diameter of 350 mm, and the conductivity of the added deionized water is ≤0.5 μs / cm.

[0053] The drying in step S3 comprises the following steps: pouring the filtered powder into a 304 stainless steel disc with a diameter of 300 mm, and placing it in a vacuum oven at 180° C. for 9 hours.

[0054] Embodiment 3:

[0055] A method for removing impurities from tantalum powder using mixed acid comprises the following steps:

[0056] S1: The capacitor-grade tantalum powder is subjected to the first stage of ultrasonic impurity removal treatment in solution A, and acetic acid is first used to remove the organic matter wrapped around the tantalum powder, so that the surface of the tantalum powder is more exposed to the acid solution;

[0057] S2: subjecting the tantalum powder treated in step S1 to a second high-temperature ultrasonic impurity removal treatment in a mixed acid solution to achieve an impurity removal effect;

[0058] S3: The tantalum powder treated in step S2 is then subjected to a third stage of ultrasonic impurity removal treatment at room temperature in a mixed acid solution to achieve a further impurity removal effect; finally, the tantalum powder is rinsed, filtered, and dried.

[0059] In the two mixed acid treatments, hydrofluoric acid first destroys the oxide layer on the tantalum surface, and non-oxidizing acid sulfuric acid can better remove Cr metal. Adding ultrasonic vibration can better open the pores of tantalum powder, allowing the acid to enter the interior of tantalum powder, allowing the metal impurities inside the tantalum powder to fully react with the mixed acid, achieving the effect of significantly reducing metal impurities such as Cr and Fe.

[0060] In step S1, solution A is a 7% acetic acid solution, which is stirred at 160 r / min and 65° C. for 12 min, and 25 KHz ultrasonic high-frequency vibration is added during the treatment process.

[0061] The mixed acid solution in step S2 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 10%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 28:1.

[0062] In step S2, the pickling is carried out under stirring at 140 r / min and 65° C. for 3 hours, and 25 KHz ultrasonic high-frequency vibration is added during the treatment process.

[0063] The mixed acid solution in step S3 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 7%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 30:1.

[0064] In step S3, the pickling is carried out under stirring at 150 r / min and 60° C. for 3 hours, and 25 KHz ultrasonic high-frequency vibration is added during the treatment process.

[0065] The rinsing in step S3 is after the acid liquid is poured out. Since the acid liquid cannot be poured out completely, 13L of deionized water needs to be added to the tantalum powder and stirred evenly before pouring out the liquid to reduce the concentration of the remaining acid liquid.

[0066] The rinsing in step S3 is after the acid liquid is poured out. Since the acid liquid cannot be poured out completely, 10L of deionized water needs to be added to the tantalum powder and stirred evenly before pouring out the liquid to reduce the concentration of the remaining acid liquid.

[0067] The filtration in step S3 includes the following steps: using a filter membrane to be laid in a filtration device with a diameter of 350 mm, pouring the powder after rinsing onto the filter membrane, vacuuming the solution to pass through the polypropylene filter membrane, and leaving the powder on the filter membrane to achieve solid-liquid separation; by continuously adding deionized water to the filtration device to dilute the acid content in the powder until the conductivity of the filtered liquid is ≤50μs / cm, stopping adding deionized water and draining the liquid in the powder.

[0068] The filter membrane is a polypropylene filter membrane with a pore size of 6 μm and a diameter of 350 mm, and the conductivity of the added deionized water is ≤0.5 μs / cm.

[0069] The drying in step S3 comprises the following steps: pouring the filtered powder into a 304 stainless steel disc with a diameter of 300 mm, and placing it in a vacuum oven at 150° C. for 6 hours.

[0070] Comparative Example 1:

[0071] A method for removing impurities from tantalum powder using mixed acid is basically the same as Example 3, except that sulfuric acid is replaced by nitric acid.

[0072] Comparative Example 2:

[0073] A method for removing impurities from tantalum powder using a mixed acid is basically the same as Example 3, except that sulfuric acid is replaced with nitric acid, the mixed acid solution in step S2 is a 20% concentration of nitric acid and hydrofluoric acid mixed acid solution, and the mixed acid solution in step S3 is a 25% concentration of nitric acid and hydrofluoric acid mixed acid solution.

[0074] The tantalum powders prepared by Examples 1-3 and Comparative Examples 1-2 were tested, and the results are shown in Table 1.

[0075] Table 1 Parameter comparison between the prior art and this method

[0076]

[0077] It can be seen from Table 1 that the Cr and Fe removal rates of Examples 1-3 are higher than those of Comparative Examples 1 and 2. Among them, Comparative Example 2 has a certain effect on the removal of Cr and Fe by increasing the acid concentration, but it is not better than the Cr and Fe removal rates of Examples 1-3, and the yield is reduced. Therefore, the method of increasing the mixed acid concentration is not the best method.

[0078] The concentration and ratio of the mixed acid in this method are not limited to the above ratios and can be selected according to the production process requirements;

[0079] The ultrasonic frequency of the present method is not limited to the above values ​​and can be selected according to the production process requirements.

Claims

1. A method for removing impurities from tantalum powder using mixed acid, characterized in that: The following steps are involved: S1: subjecting tantalum powder to the first stage of ultrasonic impurity removal treatment in solution A; S2: subjecting the tantalum powder treated in step S1 to a second high-temperature ultrasonic impurity removal treatment in a mixed acid solution; S3: The tantalum powder treated in step S2 is then subjected to a third stage of ultrasonic impurity removal treatment at room temperature in a mixed acid solution; finally, the tantalum powder is rinsed, filtered, and dried.

2. A method for removing impurities from tantalum powder using mixed acid as claimed in claim 1, characterized in that: In step S1, solution A is an acetic acid solution with a concentration of 2% to 10%, which is stirred for 10 to 15 minutes at 100 to 180 r / min and 50 to 80° C., and ultrasonic high-frequency vibration of 20 to 35 KHz is added during the treatment process.

3. The method for removing impurities from tantalum powder by using mixed acid as claimed in claim 1, characterized in that: The mixed acid solution in step S2 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 7% to 13%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 20-40:

1.

4. The method for removing impurities from tantalum powder by using mixed acid as claimed in claim 1, characterized in that: In the step S2, the pickling is carried out under stirring at 100 r / min to 180 r / min and 50° C. to 80° C. for 2 h to 4 h, and ultrasonic high-frequency vibration of 20 KHz to 35 KHz is added during the treatment process.

5. The method for removing impurities from tantalum powder using mixed acid as claimed in claim 1, characterized in that: The mixed acid solution in step S3 is a mixed acid solution of sulfuric acid and hydrofluoric acid with a concentration of 3% to 9%, and the concentration ratio of sulfuric acid to hydrofluoric acid is 20 to 40:

1.

6. The method for removing impurities from tantalum powder using mixed acid as claimed in claim 1, characterized in that: In step S3, pickling is carried out under stirring at 100 r / min to 180 r / min and 50° C. to 80° C. for 2 h to 4 h, and ultrasonic high-frequency vibration of 20 KHz to 35 KHz is added during the treatment process.

7. The method for removing impurities from tantalum powder using mixed acid as claimed in claim 1, characterized in that: The rinsing in step S3 is to pour out the acid solution, add deionized water to the tantalum powder, stir evenly, and then pour out the liquid.

8. The method for removing impurities from tantalum powder using mixed acid as claimed in claim 1, characterized in that: The filtration in step S3 comprises the following steps: using a filter membrane to be laid in a filtration device, pouring the powder after rinsing onto the filter membrane, and vacuuming the solution to pass through the polypropylene filter membrane, and the powder remains on the filter membrane to achieve solid-liquid separation; by continuously adding deionized water to the filtration device to dilute the acid content in the powder until the conductivity of the filtered liquid is ≤50μs / cm, stopping adding deionized water, and draining the liquid in the powder.

9. A method for removing impurities from tantalum powder using mixed acid as claimed in claim 8, characterized in that: The filter membrane is a polypropylene filter membrane with a pore size of 2 μm to 10 μm, and the conductivity of the added deionized water is ≤0.5 μs / cm.

10. The method for removing impurities from tantalum powder using mixed acid according to claim 1, characterized in that: The drying in step S3 comprises the following steps: placing the filtered powder into a vacuum oven at 120-180° C. for 3-9 hours.

Citation Information

Patent Citations

  • Manufacturing process of tantalum particles

    CN114472883A

  • Leaching method of nickel-based superalloy

    CN118460860A